2013
DOI: 10.1093/hmg/ddt317
|View full text |Cite
|
Sign up to set email alerts
|

A genome-wide association study of atopic dermatitis identifies loci with overlapping effects on asthma and psoriasis

Abstract: Atopic dermatitis (AD) is the most common dermatological disease of childhood. Many children with AD have asthma and AD shares regions of genetic linkage with psoriasis, another chronic inflammatory skin disease. We present here a genome-wide association study (GWAS) of childhood-onset AD in 1563 European cases with known asthma status and 4054 European controls. Using Illumina genotyping followed by imputation, we generated 268 034 consensus genotypes and in excess of 2 million single nucleotide polymorphisms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
153
1
6

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 197 publications
(172 citation statements)
references
References 79 publications
(93 reference statements)
12
153
1
6
Order By: Relevance
“…9,12,27 There is evidence that psoriasis may be associated with asthma risk. 8,21,28 A longitudinal study by Fang et al 8 indicated that a psoriasis population has an increased risk of developing asthma. Asthma is a chronic inflammatory disorder of the airway that is caused by multiple factors that involve environmental, genetic, and immunologic factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9,12,27 There is evidence that psoriasis may be associated with asthma risk. 8,21,28 A longitudinal study by Fang et al 8 indicated that a psoriasis population has an increased risk of developing asthma. Asthma is a chronic inflammatory disorder of the airway that is caused by multiple factors that involve environmental, genetic, and immunologic factors.…”
Section: Discussionmentioning
confidence: 99%
“…32 Further studies indicate that genetic risk loci might be partially overlapped between asthma and psoriasis. 11,28,33 Interestingly, studies also found that psoriasis is associated with an increased risk of migraine and chronic obstructive pulmonary disease. 34,35 TNF-␣ has been shown to promote the pathogenesis of migraine by sensitization of meningeal nociceptors and peripheral nerve endings through activation of the p38 mitogen-activated protein kinases pathway, 36 and elevation of TNF-␣, interferon ␥, and IL-23 in patients with psoriasis could lead to an increased risk of chronic obstructive pulmonary disease by causing pulmonary inflammatory responses.…”
Section: Discussionmentioning
confidence: 99%
“…GWA studies have identified a strong relationship between the common SNP rs4722404 in CARD11 and AD (Hirota et al, 2012;Weidinger et al, 2013). Genetic evidence has demonstrated a higher level of genomic similarities between AD and psoriasis (Weidinger et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Genetic evidence has demonstrated a higher level of genomic similarities between AD and psoriasis (Weidinger et al, 2013). However, the effect of the SNP rs4722404 on the risk and clinical features of psoriasis, as well as the biological mechanism underlying this role, remain unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation